Improvements within the peanut production chain to minimize aflatoxins contamination: An Ethiopian case study. (June 2022) - Cervini, Carla; Verheecke-Vaessen, Carol; He, Tingting; Mohammed, Abdi; Magan, Naresh; Medina, Angel
Abstract: Peanuts ( Arachis hypogaea L.) are a worldwide crop appreciated by consumers and known to have several health benefits (e.g. decreasing risk of cardiovascular diseases, lowering LDL cholesterol). Nonetheless, during the production chain, peanuts can be contaminated by mycotoxigenic fungi, especially Aspergillus flavus and A. parasiticus, responsible for contamination of this commodity with aflatoxins (AFs). Chronic exposure to these mycotoxins is known to have carcinogenic, teratogenic and immunosuppressive effects, while acute exposure can be fatal. Peanut-based products are considered the "new-gold" in Lower Middle-Income Countries (LMICs) as they are used to produce therapeutic food to fight malnutrition in children in the form of high energy bars (e.g. Plumpy'Nut®). The present study has been focused on an examination of the existing Ethiopian peanut supply chain to identify components that require improvements during pre-harvest, harvesting and post-harvest where practical and affordable intervention practices can be implemented. The lack of Good Agricultural Practices (GAPs), the use of traditional and rudimentary methods for drying and shelling peanuts, as well as inadequate storage locations are some of the main factors associated with the high contamination of Ethiopian peanuts with AFs. While control of AFs is complex, in-depth examination of existing practices has facilitated an overview of the potential for efficient and low-cost strategies to reduce and minimize these toxin risks in the Ethiopian peanut production chain. This includes the use of Drycard™ as a tool to check moisture content, the creation of homemade solar dryer and wooden nutcrackers, and the use of either the Purdue Improved Crop Storage (PICS) bags or novel bags with slow-release food-grade preservatives. The implementation of some of these approaches should ensure a safer home-grown peanut supply chain that would contribute to the growth of the economy of the country by reducing the high costs of importing such raw materials and supporting the use of local smallholder farmers peanuts. This would have significant economic benefits in the local peanut production chain. Highlights: Peanuts are "new gold" in LMICs for ready-to-use therapeutic foods for malnutrition. Ethiopian peanuts are susceptible to Aspergillus section Flavi spoilage and aflatoxins (AFs). Critical factors which represent a high risk of toxin contamination along the chain are highlighted. Practical and economic mitigation solutions are proposed to reduce AFs in the Ethiopian peanut chain.